Clinical and Functional Outcomes of Total Knee Arthroplasty in Sarcopenia: A Case–Control Retrospective Cohort Study - He, Zili; Cai, Jie; Wang, Xingyu; Lu, Di (The Journal of Knee Surgery, 2021)
Background The aim of the study was to investigate the relationship between sarcopenia and both clinical and functional outcome scores following total knee arthroplasty (TKA) performed for patients over 65 years of age.Methods We assessed patient demographics, preoperative health status, postoperative Knee Society Clinical (KSS-C) and Function (KSS-F) subscores, and perioperative complications for 180 patients with sarcopenia and 345 comparatively healthy patients at a mean of 12.0 months after surgery. Multivariate logistic regression analysis was performed to define whether sarcopenia was an independent risk factor for lower KSS-F and KSS-C subscores and peroperative complication rates. Patients with sarcopenia had lower mean body mass index, preoperative albumin, and preoperative hemoglobin levels (p < 0.01).Results Compared with the healthy control group, patients with sarcopenia had lower KSS-C (83.0 vs. 88.2, p < 0.01) and KSS-F (79.2 vs. 86.1, p < 0.01) subscores and increased postoperative complication rates (14.1% vs. 4.1%, p < 0.01).Conclusion Patients with sarcopenia present with generally poorer preoperative health and this appears to be associated with lower patient-reported clinical and functional outcome scores. Complication rates were higher among patients with sarcopenia who were still determined to have adequate health status to support TKA. Most complications were limited and could be managed with supportive treatment.
Keywords: complications; KSS-C; KSS-F; sarcopenia; total knee arthroplasty